Sacred biography in the Buddhist traditions of South and Southeast Asia - Schober, Juliane (University of Hawai'i Press, 1997)
This collection of previously unpublished essays presents a broad range of explorations into the biographical genre of the Buddhist traditions of South and Southeast Asia. Each contribution examines sacred biography in one or more representational modalities in the texts, art history, literature, myths, rituals and cultures of the Buddhist tradition. Scholars in the history of religions, anthropology, literature and art history present a broad range of explorations into sacred biography as an interpretive genre. The essays investigate both universal and local articulations of Buddhist sacred biography, illustrating the construction of interpretive frames of reference that map salient themes onto diverse contexts. The combination of thematic depth and theoretical sophistication in Sacred Biography makes this volume innovative reading for all scholars with comparative interests.
Keywords: Gautama Buddha.; Gautama Buddha; Buddhist saints -- Biography -- History and criticism.; Buddhist hagiography -- History and criticism.; Saints bouddhistes -- Biographies -- Histoire et critique.; Hagiographie bouddhique -- Histoire et critique.; RELIGION -- Buddhism -- General.; Buddhist hagiography; Buddhist saints -- Biography; Electronic books.; Criticism, interpretation, etc.